Observation on the curative effect of umbilicus application therapy combined with Cucurbit moxibustion in the treatment of spleen deficiency syndrome of type 2 diabetes mellitus (敷脐疗法联合葫芦灸治疗2型糖尿病脾虚证疗效观察) - GAO Junluan (高俊娈); XUE li (薛丽); ZHANG Gengliang (张庚良); HAO Min (郝民); MAO Hui (毛慧); SHEN Yanru (沈彦如) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of umbilical application therapy combined with Cucurbit moxibustion on improving blood glucose level and Traditional Chinese Medicine (TCM) syndrome score of spleen deficiency in type 2 diabetic patients, and evaluate its clinical efficacy. Methods Using convenience sampling method, 60 patients with type 2 diabetes admitted to our hospital from March 2020 to December 2020 were selected as the research objects, and randomly divided into two groups, 30 people in each group. The control group was treated with metformin plus umbilical application therapy, and the treatment group was treated with moxibustion on the basis of the control group. The spleen deficiency symptom score, blood glucose level and clinical effect of spleen deficiency were observed before and after intervention. Results There were statistically significant differences in spleen deficiency symptom score, fasting blood glucose (FBG) and 2-hour postprandial blood glucose (2hPBG) before and after treatment (P<0. 05). After intervention, the total score of spleen deficiency symptom, FBG level and 2hPBG level in the treatment group were lower than those in the control group (P<0. 05). In terms of clinical efficacy, the total effective rate of the treatment group (93. 33%) was higher than that of the control group (80%), with a significant difference (P<0. 05). Conclusion Umbilical application therapy combined with Cucurbit moxibustion can effectively regulate blood glucose level and improve spleen deficiency syndrome score for patients with type 2 diabetes, and its clinical efficacy is superior to umbilical application therapy, which is worthy of clinical promotion (目的 观察敷脐疗法联合葫芦灸改善2型糖尿病脾虚症患者的血糖水平和脾虚中医症候积分的效果, 评价其临床疗效。方法 采取便利抽样法, 选取2020年3月-12月医院收治的60例2型糖尿病患者为研究对象, 随机分为对照组和治疗组, 各30例。对照组采用二甲双胍加敷脐疗法, 治疗组在对照组基础上增加葫芦灸治疗。观察干预前后患者脾虚症状积分、血糖水平以及脾虚临床疗效变化。结果 两组患者治疗前后脾虚症状积分、空腹血糖(FBG)、早餐后2 小时(2hPBG)血糖比较, 差异有统计学意义(P＜0. 05); 干预后治疗组在脾虚症状总积分、FBG、2hPBG血糖低于对照组义(P＜0. 05)。临床疗效评价, 治疗组总有效率(93. 33％)高于对照组总有效率(80. 00％), 差异有统计学意义(P＜0. 05)。结论 对2型糖尿病脾虚证患者, 采用敷脐疗法联合葫芦灸治疗可以有效调节血糖水平, 改善脾虚中医症状积分, 其临床疗效优于单用敷脐疗法治疗。)